THE CONCEPT OF THE «BLACK HUNDREDS» IN THE SOVIET HISTORICAL SCIENCE: RUNNING IN CIRCLES - Ivakin, G. A. (Vestnik MGIMO-Universiteta, 2016)
During the Soviet period, the right monarchism was considered by historians of our country as part of general methodological approaches to the study of non-proletarian parties. As ideological and political antagonist of Bolshevism, the Black Hundreds were interpreted as the most reactionary political movement of pre-revolutionary Russia. As a result, the full scientific debate on the right monarchism in the Soviet period did not take place, and Soviet historians failed to form a historical concept of the Black Hundreds as an ideological and political trend in the early twentieth century.